1978
DOI: 10.1093/bja/50.10.993
|View full text |Cite
|
Sign up to set email alerts
|

E.E.G. Monitoring for the Control of Anaesthesia Produced by the Infusion of Althesin in Primates

Abstract: The continuous infusion of Althesin under electroencephalographic (e.e.g.) control provided a constant level of light anaesthesia for periods of 1--5.5 h during experimental brain hypoxia in spontaneously breathing baboons and Rhesus monkeys. Polygraphic records (respiration, heart rate, arterial pressure, cerebral venous sinus pressure, end-tidal gas concentrations) and also estimation of blood-gas tensions, pH, and concentrations of pyruvate and lactate demonstrated a steady physiological state. Various meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…However, it was concluded that the alfaxalone–alfadolone combination decreased the dominating EEG frequencies, caused increasing degrees of burst suppression and even complete electrical silence at higher doses (Fitch et al. 1978; Prior et al. 1978; Saady & Hicks 1980; Ogawa 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was concluded that the alfaxalone–alfadolone combination decreased the dominating EEG frequencies, caused increasing degrees of burst suppression and even complete electrical silence at higher doses (Fitch et al. 1978; Prior et al. 1978; Saady & Hicks 1980; Ogawa 1987).…”
Section: Discussionmentioning
confidence: 99%
“…There are publications about the effects of the alfaxalone–alfadolone combinations on the EEG of humans, primates and cats (Fitch et al. 1978; Prior et al. 1978; Saady & Hicks 1980; Ogawa 1987) but not of dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) according to the global stage analysis chart of Prior, et al 9 and they remained constant over an arterial pressure range of 120-40 mm Hg. The scatter of the individual recordings is shown in figure 4.…”
Section: Electroencephalogrammentioning
confidence: 95%
“…These strips were later analyzed using a 5-point visual inspection scale modified from a scale described by Prior et al (1978). Details of the grading scale have been described elsewhere (DeWitt et al, 1992a;1992b).…”
Section: Animal Preparationmentioning
confidence: 99%